Nagari dan Desa dalam Otonomi Desa: Sebuah Perspektif Komparatif - Frans Tory Damara Pradipta Frans Tory Damara Pradipta (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2025)
This study explores the significance of village autonomy in Indonesia through a comparative analysis between nagari in West Sumatra and administrative villages (desa) across the country. The purpose of this research is to understand how both entities reflect different models of autonomy within the framework of community-based local governance. Using a qualitative comparative literature approach, this study examines legal documents, historical sources, and previous research, while also drawing comparative insights from barangays in the Philippines and customary villages in Negeri Sembilan, Malaysia. The findings show that nagari demonstrates a stronger capacity in fostering social cohesion, deliberative decision-making, and communal land management, whereas desa is more effective in ensuring bureaucratic accountability and alignment with national development programs. These results highlight that village autonomy in Indonesia represents a dynamic negotiation between traditional legitimacy and modern administrative governance. The study contributes to the development of a more inclusive and contextual model of local governance that harmonizes cultural values with administrative effectiveness.